Bioactivity Formulation Of Leaf Extract Of Kalanchoe pinnata And Seed Of Azadirachta indica Against Spodoptera litura - Paramita, Hedi; Puspasari, Lindung Tri; Maharani, Rani; Supratman, Unang; Hidayat, Yusup; Meliansyah, Rika; Dono, Danar (CROPSAVER - Journal of Plant Protection, 2018)
The aim of this research is to know the most effective concentration of liquid formulation of Kalanchoe pinnata leaf extract 50 EC and Azadirachta indica seed extract 50 EC against S. litura. The experiment was conducted at the Laboratory of Pesticides and Enviromental Toxicology, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Padjadjaran. The concentration were tested of each formulation were 1%, 2%, 3 %, 4%,and control.  The experiment arranged in completely randomized design (CRD) and replicated three times. The results showed that the formulation of A. indica seed extract 50 EC at concentration of 2%, 3%, and 4% effective against S. Litura larvae with mortality of 76.7%, 86.7, and 93.3%  This formulation also causing a decrease in feeding activity, weight, and lenghten the development time of S.litura larvae. Unlike the case with liquid formulations of K. pinnata 50 EC extract which was less toxic and did not show significant differences in feed intake, weight of larvae, and development time of larvae compared control treatment.                Keywords: Toxicity, mortality, growth dearragement, botanical insecticide.